Perception of Dental Students on Online Learning - Alifia Ummu Risya; Putu Hiroko Anindya; Muhammad Raidjffan Z.T; R. Devathara Ardhisatrya; Seno Fauzi Alyanugraha; Muhammad Zaydan; Nastiti Faradilla Ramadhani (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Online learning can overcome the shortage of teaching staff and has the potential to change the passive learning process into active learning which depends on the willingness of students through their views on the concept of online learning. Purpose: To know the perception of students of the Faculty of Dental Medicine, Universitas Airlangga, Surabaya, Indonesia on online learning. Methods: Perception was obtained using simple random sampling technique through distributing questionnaires in the form of google form containing 14 questions with a choice of answers; completely disagree, disagree, do not know, agree, and completely agree with the active students of the Faculty of Dental Medicine, Universitas Airlangga from the class of 2016, 2017, 2018 regarding the student’s views on online learning. Results: it shows that almost all Dental Medicine students have a computer and access to the internet (75% completely agree, 25% agree) know how to open and open, modify and upload documents online (61% completely agree, 36.4% agree), and access internet with daily or weekly use (59% completely agree, 36.4% agree). Conclusion: Students’ perceptions of the Faculty of Dental Medicine, Universitas Airlangga, Surabaya, Indonesia are ready to use online learning methods .